Reconstructing the Harmonization of Customary Law and National Law in the Formulation of Public Policy Based on Living Law in Indonesia - Sitti Fausia; Perdana Herryanto Sultan (Journal of Social Research, 2026)
Indonesia’s plural legal system reflects the coexistence of national law, customary law, and other normative orders; however, the harmonization of customary law within public policy remains incomplete and often results in legal uncertainty, conflict, and limited social legitimacy. This study aimed to reconstruct a living-law-based model for harmonizing customary law and national law in public policy formulation in Indonesia. The research employed normative legal research using statutory, conceptual, comparative, and case approaches. Legal materials included constitutional provisions, legislation, court decisions, scholarly literature, and government policy documents, which were analyzed qualitatively through systematic, historical, and teleological interpretations. The findings revealed that disharmony persists in the recognition of customary law communities, natural resource management, and dispute resolution because sectoral regulations and administrative mechanisms have not fully accommodated living customary norms. This study proposed a five-stage harmonization model consisting of the identification of living customary values, synchronization with statutory law, participation of customary communities, context-sensitive policy implementation, and periodic evaluation. The study concluded that legal harmonization should integrate relevant customary values without compromising legal certainty, human rights, and the rule of law, thereby supporting more inclusive, responsive, legitimate, and substantively just public policies in Indonesia within the framework of its contemporary plural legal order.